Mimicking the Opposition: Bismarck's Welfare State and the Rise of the Socialists - Felix Kersting (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2023)
This paper examines the consequences of a government mimicking the policy of its competitor by studying the introduction of the welfare state in 19th century Germany. The reform conducted by the conservative government targeted blue-collar workers and aimed to reduce the success of the socialist party. The result based on a difference-in-differences design shows that the socialist party benefited in elections due to the reform. The analysis of the mechanism points to the socialist's issue ownership by strengthening its reform orientation, which voters followed. The results are not driven by other political and economic channels related to the reform.
Keywords: D74; H53; I38; N44; P16; 330; welfare state; socialism; government; opposition; issue ownership; voting behavior; Germany